2012
DOI: 10.1097/olq.0b013e31825f7af7
|View full text |Cite
|
Sign up to set email alerts
|

HIV and Associated Risk Factors Among Male Clients of Female Sex Workers in a Chinese Border Region

Abstract: Background Male clients of female sex workers (FSWs) serve as a potential bridge of HIV to the general population. Little is known about the characteristics and risk factors for HIV infection among male clients patronizing FSWs in Hekou County, Yunnan Province in southern China bordering with Vietnam. Methods Male clients were recruited through outreach of study staff, referrals by Vietnamese FSWs, their bosses, and snowball sampling. Each participant completed a questionnaire survey and donated a blood spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 23 publications
1
31
3
Order By: Relevance
“…Three studies reported a median annual income between 1300–2000 US$ [42], [45], [46]. In the other three studies, 40% of participants earned less than 1700 US$ per year [47], 65% earned less than 2900 US$ per year [43], and 33% earned less than 800 US$ per year [48].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three studies reported a median annual income between 1300–2000 US$ [42], [45], [46]. In the other three studies, 40% of participants earned less than 1700 US$ per year [47], 65% earned less than 2900 US$ per year [43], and 33% earned less than 800 US$ per year [48].…”
Section: Resultsmentioning
confidence: 99%
“…Six studies were undertaken in south central China [45], [49]–[53], eleven in the southwest [12], [38], [42], [44], [46]–[48], [53]–[56], eleven in the east [36], [37], [39], [41], [57]–[63], and seven in the north [64]–[70]. Two studies were national [4] or multi-city samples [71].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Globally, FSW have a 13.5 times greater odds of living with HIV than non-FSW women 17 . Given that inconsistent condom use is prevalent among male clients in LMIC 10,1820 , ensuring that male clients who are infected with HIV are tested and connected to care and treatment may be one of the most effective ways to stem HIV transmission among male clients, their non-commercial sexual and drug partners, and FSW.…”
Section: Introductionmentioning
confidence: 99%